2022
DOI: 10.1002/cbin.11793
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin and l‐carnitine combination therapy alters the erythrocytes redox status

Abstract: Hematopoiesis is a sensitive target of artemisinin (ART) and its derivatives, and hemolysis is one of their commonly reported side effects. L-carnitine (LC), an amino acid derivative involved in lipid metabolism, is beneficial for hematological parameters. Sixty adult laboratory mice were randomly divided into six groups.Group I (control) received saline and corn oil; groups II and III received therapeutic (50 mg/kg) and toxic (250 mg/kg) doses of ART, respectively; groups IV and V received 370 mg/kg LC along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In severe cases, immediate medical intervention is required to stabilize the patient and prevent further complications [10]. Artemisinins have toxic effects on erythropoiesis in both animal and human studies [11]. A report showed that 70-80% of rural communities rely on medicinal plants for primary treatment and traditional and contemporary medicine, with impoverished individuals in developing nations relying on these plants because of their unique nutritional pro le [12].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, immediate medical intervention is required to stabilize the patient and prevent further complications [10]. Artemisinins have toxic effects on erythropoiesis in both animal and human studies [11]. A report showed that 70-80% of rural communities rely on medicinal plants for primary treatment and traditional and contemporary medicine, with impoverished individuals in developing nations relying on these plants because of their unique nutritional pro le [12].…”
Section: Introductionmentioning
confidence: 99%